Effectiveness of Internal Control Systems Over Cash Receipts and Disbursements Procedures at PT. Kumon Indonesia - Rachma Novianti, Dinda; Wardatul Afiqoh, Nyimas (Indonesian Vocational Research Journal, 2025)
This study aims to analyze the effectiveness of the internal control system over cash receipt and disbursement procedures at PT. Kumon Indonesia Gresik Branch. In this era of rapid digitalization, the need for a transparent and accountable financial management system has become very important, especially in the education sector. This study uses a qualitative descriptive approach with data collection methods through interviews, observation, and documentation. The results of the study indicate that PT. Kumon Indonesia Gresik Branch has implemented several key principles of internal control, such as the use of valid transaction documents, separation of duties between administrators and business owners, and manual and computerized transaction recording. However, there are still weaknesses, including overlapping duties between the administrative department and business owners, the absence of formally documented standard operating procedures (SOPs), and inadequate monitoring. Therefore, it is recommended that the company strengthen the separation of functions, establish clear and documented SOPs, and increase the frequency of monitoring and evaluation. With these improvements, it is expected that the effectiveness of internal control will increase, thereby preventing fraud, enhancing the reliability of financial reports, and strengthening stakeholders' confidence in the company's financial management.